An Unusual Presentation of Giant Schwannoma of Hand: A Case Report - KC, Sudeep; Pathak, Roshani (Nepalese Journal of Radiology, 2024)
Peripheral nerve sheath tumors are uncommon. Peripheral nerve tumors (PNTs) constitute less than 5% of all hand tumors. Schwannomas, also known as neurolemmas, are benign tumors of the peripheral nerve sheath arising from Schwann cells. The median nerve schwannomas account for 0.1-0.3% of all cases. Here is a case of a seventeen-year-old male who presented with a painless lump on the thenar aspect of the left hand simulating lipoma clinically. The patient underwent various imaging modalities including Magnetic Resonance Imaging (MRI) which suggested a peripheral nerve sheath tumour most likely Schwannoma. The lesion was excised under the regional block and was confirmed as Schwannoma histologically.